Streptomyces colonosanans sp. nov., A Novel Actinobacterium Isolated from Malaysia Mangrove Soil Exhibiting Antioxidative Activity and Cytotoxic Potential against Human Colon Cancer Cell Lines - Law, Jodi Woan-Fei; Ser, Hooi-Leng; Duangjai, Acharaporn; Saokaew, Surasak; Bukhari, Sarah I.; Khan, Tahir M.; Ab Mutalib, Nurul-Syakima; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2017)
Streptomyces colonosanans MUSC 93JT, a novel strain isolated from mangrove forest soil located at Sarawak, Malaysia. The bacterium was noted to be Gram-positive and to form light yellow aerial and vivid yellow substrate mycelium on ISP 2 agar. The polyphasic approach was used to determine the taxonomy of strain MUSC 93JT and the strain showed a range of phylogenetic and chemotaxonomic properties consistent with those of the members of the genus Streptomyces. Phylogenetic and 16S rRNA gene sequence analysis indicated that closely related strains include Streptomyces malachitofuscus NBRC 13059T (99.2 % sequence similarity), Streptomyces missionensis NBRC 13063T (99.1 %) and Streptomyces phaeoluteichromatogenes NRRL 5799T (99.1 %). The DNA–DNA relatedness values between MUSC 93JT and closely related type strains ranged from 14.4 ± 0.1 % to 46.2 ± 0.4 %. The comparison of BOX-PCR fingerprints indicated MUSC 93JT exhibits a unique DNA profile. The genome of MUSC 93JT consists of 7,015,076 bp. The DNA G + C content was determined to be 69.90 mol%. The extract of strain MUSC 93JT was demonstrated to exhibit potent antioxidant activity via ABTS, metal chelating, and SOD assays. This extract also exhibited anticancer activity against human colon cancer cell lines without significant cytotoxic effect against human normal colon cells. Furthermore, the chemical analysis of the extract further emphasizes the strain is producing chemo-preventive related metabolites. Based on this polyphasic study of MUSC 93JT, it is concluded that this strain represents a novel species, for which the name Streptomyces colonosanans sp. nov. is proposed. The type strain is MUSC 93JT (=DSM 102042T =MCCC 1K02298T).